Effect of exergame training with motor imagery on balance, cognitive functions and motor learning in healthy adults: Preliminary study - Srisupornkornkool, Kanokwan; Ploypai, Benjaporn; Sripolnoi, Siriwan; Kaewmanee, Araya; Amphat, Tawit; Thammajak, Thammajak; Munrod, Tunwa; Opasanon, Nattaporn; Boonyarom, Onuma; Somthavil, Sompiya (Chulalongkorn Medical Journal, 2023)
Background: Previous studies reported that exergames could improve balance and cognitive function. Also, motor imagery (MI) applied with actual movements could increase balance control. If both are combined, balance and cognitive function may increase more. Objective: To investigate the effect of exergame training with MI on balance, cognitive function and motor learning in healthy adults. Methods: Twelve subjects were divided into 2 groups, the exergame training (ET, n = 6) and the exergame with MI training (ET + MI, n = 6). Both groups practiced exergame for 20 minutes. Then, the ET+ MI group imagined exergame for 10 minutes. Subjects were trained 3 days per week for a period of 4 weeks. Balance and cognitive function were assessed before training, after 4 weeks of training, and in the follow-up period. Results: The results showed a significant increase in the single-leg stance test and trunk position sense found only in the ET + MI group, whereas % performance of static balance was significantly increased in both groups after 4 weeks of training and in the follow-up period (P < 0.05). Cognitive functions significantly improved in both groups in the follow-up period when compared with before training, except a corsi task in the ET group were greater in the follow-up period (P < 0.05). Conclusion: The ET with MI could facilitate better balance abilities. Interestingly, motor learning could be observed in the retention period in both training programs.